2010
DOI: 10.1145/1805961.1805962
|View full text |Cite
|
Sign up to set email alerts
|

A taxonomy of visualization strategies for cultural heritage applications

Abstract: In this article we present a general classification of the different approaches that might be employed to constitute a visual representation of a cultural heritage item, including the ones featuring the use of traditional tools as the ones exhibiting the inclusion of modern 2D and 3D digital technologies. In order to establish a coherent taxonomy, specific elements characterizing such approaches will be discussed and employed to assist the definition of a general conceptual framework that will enable the class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 24 publications
0
30
0
3
Order By: Relevance
“…An international science community has been shaped by actors from Southern Europe, Great Britain and the US. It mainly comprises perspectives on archaeology and cultural heritage conservation (European Commission, 2011;Foni et al, 2010;Münster et al, in print). A multiplicity of actors from science, economy and education deal with the topic of digital reconstruction in the German-speaking area.…”
Section: State-of-the-artmentioning
confidence: 99%
“…An international science community has been shaped by actors from Southern Europe, Great Britain and the US. It mainly comprises perspectives on archaeology and cultural heritage conservation (European Commission, 2011;Foni et al, 2010;Münster et al, in print). A multiplicity of actors from science, economy and education deal with the topic of digital reconstruction in the German-speaking area.…”
Section: State-of-the-artmentioning
confidence: 99%
“…Though focusing on parameters of the technological classifications, the article, in which the complex model was presented, showed that the four dimensions had different value to people, depending on their role. It demonstrated that 'content consumers' (audience) saw visual consistency as a necessity, and precision as an option, whereas automatism and interactivity was deemed unnecessary, while 'content holders' (historians and archaeologists) on the contrary valued precision over optional visual consistency and the unnecessary automatism [37]. Not only this roledependant evaluation of audio-visual media describes its status in museums.…”
Section: Previous Definitionsmentioning
confidence: 99%
“…Liu [14] mentioned the mental models for visual reasoning and interaction, which links the interactive representation with the mental models and external visualization. There are proposed many other taxonomies with its own classification method, and they all aim at visualization in specific areas of application, such as medicine, history [11], finance [1], etc. There is even a "periodic system of visualization methods" which pretended to be the basic concentrated concept of successfully used methods for data visualization until now.…”
Section: Related Workmentioning
confidence: 99%